Are Leaders’ Personality Traits Imperative For Employees’ Job Performance? The Context Of An Emerging Economy - Anwar, Bilal; Xiao, Zhongdong; Fiaz, Muhammad; Ikram, Amir; Younas, Muhammad (Journal of Applied Business Research, 2017)
Leader’s personality considerably influences the behavior of employees and is perhaps one of the most important predictor of their job performance. The purpose of the study was to evaluate the personality-performance paradigm in the context of emerging economies. Personality was assessed through big five traits, namely openness to experience, conscientiousness, extraversion, agreeableness and neuroticism. While task performance attribute of job performance was considered as dependent variable. Stratified sampling technique was deployed to gather data from 149 SMEs belonging to diversified business sectors operating in the industrial city of Gujranwala, Pakistan. Cronbach’s alpha test endorsed the consistency of survey questionnaire, and multiple regression analysis was used to test hypotheses. All of the personality traits, with the exception of neuroticism, are found to be valid predictors of employee job performance, though the degree and significance of correlation varies. The study contributes to the enhanced understanding of the personality-performance relationship and highlights the desirable personality inventories of potential leaders and entrepreneurs. Broader practical implications and recommendations for future research bring the discussion to the close.
Keywords: Big Five Traits; Employee Job Performance; Leaders; Personality; Pakistan; SMEs